Subtotal petrosectomy - a tertiary center’s experience - Branco, Pedro (2024)
Introduction: Subtotal Petrosectomy (SPT) is an effective and definitive solution in cases of recurrent chronic otitis media. The expansion of its indications demonstrates its usefulness and safety in resolving various challenging otologic pathologies. Materials and Methods: A retrospective study of 25 patients (26 ears) who underwent SPT was conducted. Data regarding the indication, surgical procedures performed, complications, and clinical outcomes were collected. Results: Fourteen (n=14) patients with cholesteatomatous chronic otitis media (COM) were proposed for SPT due to recurrence. None of these patients (n=0) had useful hearing. Five (n=5) had facial palsy. The second most frequent indication (n=10) was COM associated with profound sensorineural hearing loss, and cochlear implantation was performed simultaneously in these cases. None (n=0) had facial palsy or disease recurrence. Other indications included tympanomastoid paraganglioma (n=1), anatomical factors in cochlear implant surgery (n=2), and intracochlear schwannoma (n=1). During the follow-up period (mean = 25 months), no signs or symptoms of recurrence were observed in these patients. Complications occurred in four cases, skin fistulization of SPT cavity (1), electrode array extrusion (1) and postoperative infection of the PST cavity (2). Conclusion: PST has proven to be a safe and effective surgical technique. PST with simultaneous cochlear implantation is a viable option for patients with COM. Surgical treatment with PST for COM should be considered when a poor audiological outcome is expected in a Canal Wall Down (CWD) mastoidectomy.